Influence of amorphous phase in LaMgAl11O19 on properties of LaMgAl11O19/YSZ thermal barrier coatings. Issue 7 (1st April 2021) - Wang, Yajun; Ma, Xinxin; Ma, Rui; Tang, Guangze; Sun, Junbin; Cao, Xueqiang
Abstract: Double ceramic layer thermal barrier coatings (DCL-TBCs) of LaMgAl11 O19 /YSZ (LMA/YSZ) were prepared by atmospheric plasma spraying (APS). Composition, microstructure and phase stability of coatings were analyzed by X-ray diffraction (XRD), scanning electron microscope (SEM) and differential scanning calorimetry (DSC). The amorphous phase content of LMA coating increased with increasing the plasma gun current from 350 A to 650 A. The DCL-TBCs of LMA/YSZ whose LMA coating was prepared with a plasma gun current of 600 A (600LMA/YSZ) had the lower amorphous phase content, an excellent thermal insulation performance and the longest thermal cycling lifetime, indicating that properties of LMA coating could be largely improved by adjusting the APS conditions.